Evaluasi Penerapan Manajemen Strategi Pada Dinas Pemuda Olahraga Dan Pariwisata Dalam Pengembangan Kepariwisataan Di Kabupaten Wajo - Herlina, Besse; Mustaking, Mustaking; Lestari, Sri Ayu; Syamsiar, Syamsiar; Aminah, Sitti (Jurnal Pemerintahan dan Politik Lokal, 2024)
Abstract: This study aims to evaluate the extent to which strategic management is implemented at the Sports and Tourism Youth Service in tourism development in Wajo District. as well as to find out the supporting and inhibiting factors for the implementation of strategic management at the Youth Sports and Tourism Office in tourism development in Wajo Regency. The research method uses qualitative research methods, which are located at Disporapar Wajo. The research targets consisted of the Head of Disporapar and Wajo Disporapar Employees. The informant determination technique used purposive sampling consisting of key informants and supporting informants. Data collection techniques consist of interviews, observation, and documentation. Research data sources consist of person, place, and paper. The results of the evaluation of the implementation of the Disporapar management strategy in tourism development in Wajo Regency show that the evaluation of the implementation of strategy management at the Youth Sports and Tourism Office in tourism development in Wajo Regency has been running effectively and efficiently and the implementation process and stages are reviewed from a good research aspect. The supporting factors in implementing strategic management at the Youth Sports and Tourism Office are the support from the government, the birth of rules and guidelines, the partnerships and collaborations that are owned and the involvement of universities. While the inhibiting factors in its development are the limited amount of the budget, as well as the lack of potential human resources in the tourism sector